Artikel Jurnal Perancangan UI/UX Mobile App Interaktif untuk Meningkatkan Promosi dan Penjualan Produk F&B pada Eatery Cafe - Desika Emil Syafitri; Firnanda Al-Islama Achyunda Putra (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
In the digital era and advances in information technology, there is a great opportunity to utilize mobile apps as a solution to overcome challenges in the current digital era. The food and beverage (F&B) industry market is increasingly competitive with the presence of various new cafes and restaurants. To maintain and increase market prey, effective product promotion becomes very important. In this context, mobile applications are a potential tool for connecting customers with the products and promotions offered by a cafe. The aim of this research is to design an interactive mobile application interface for Eatery Cafe which focuses on increasing promotions and sales of F&B products. The method used is User Centered Design (UCD), where this method is able to place the user as the main focus in the design process. This design will then offer an intuitive and attractive user experience. In this design, it allows users to explore the menu, view product promotions, order online, and interact with Eatery Cafe through the feedback feature. Apart from that, the application is also equipped with payment features that make transactions easier for customers. Evaluation of the prototype through user trials shows that this application is successful in increasing user engagement and increasing awareness of F&B product promotions. Thus, it is hoped that this application can become an effective tool in strengthening the relationship between Eatery Cafe and customers and increasing product sales.